PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI : (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2017-2020) - Sekar Arum Mitha Saraswati; Ida Nurhayati (Universitas Sains dan Teknologi Komputer, 2022)
This study was conducted to determine the effect of liquidity, leverage, profitability, and activity on profit growth. Also to determine whether fiem size can strengthen the relationship between liquidity, leverage, profitability, and activity on profit growth. The type of data used in this study is secondry data, which was obtained from the annual financial reports of manufacturing company during 2017-2020. The data analysis techniques used in this research were Descriptive Statistical, Normality Test, Classical Assumption Testing, Multiple Linear Analysis Test, F Test, Coefficient of Determination Test, Hypothesis Testing, and Moderated Regression Analysis (MRA). The result of this study indicate that liquidity and leveragehave no significance effect on profit growth, but profitability and activity indicate a positive and significant on profit growth. Meanwhile, firm size only strengthens the effect of liquidity on profit growth.